Exercise-induced up-regulation of MMP-1 and IL-8 genes in endurance horses - Cappelli, Katia (BioMed Central, 2009)
BACKGROUND: The stress response is a critical factor in the training of equine athletes; it is important for performance and for protection of the animal against physio-pathological disorders. In this study, the molecular mechanisms involved in the response to acute and strenuous exercise were investigated using peripheral blood mononuclear cells (PBMCs). RESULTS: Quantitative real-time PCR (qRT-PCR) was used to detect modifications in transcription levels of the genes for matrix metalloproteinase-1 (MMP-1) and interleukin 8 (IL-8), which were derived from previous genome-wide expression analysis. Significant up-regulation of these two genes was found in 10 horses that had completed a race of 90–120 km in a time-course experimental design. CONCLUSION: These results suggest that MMP-1 and IL-8 are both involved in the exercise-induced stress response, and this represents a starting point from which to understand the adaptive responses to this phenomenon.